Pancreas Proapoptotic Proteases in Patients with Chronic Pancreatitis - N. B. Gubegritz; E. A. Krylova; Yu. A. Gaidar (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim.  To study features of localization of the DNA-ase I and endonuclease-G proapoptotic proteases in the pancreas in chronic pancreatitis (CP). Materials and methods. Histological pancreas preparations from 60 patients with various CP forms were studied: group I — 10 patients with obstructive CP; group II — 21 patients with calcific CP; group III — 13 patients with fibroparenchymal CP; group IV — 16 patients with CP complicated by pseudocyst. Pancreas biopsies were obtained during planned organ operations, as well as using a fine-needle biopsy under ultrasound control. Tissue material was fixed in Bowen medium. Microscopic tissue sections were prepared and subsequently stained with hematoxylin-eosin and by Mallory-Slinchenko. Immunohistochemical typing of proapoptotic proteases was performed according to the indirect avidin-streptavidin-peroxidase reaction (“Elite”, USA) using rabbit antibodies to DNA-I and endonuclease-G (“Chemicon”, USA, 1: 500 dilution — 1: 2000, incubation 12:00, + 4 °С).Results. Patients in all the groups demonstrated signs of chronic inflammation, with 31.7 % of cases showing signs of its exacerbation. Atrophic changes were found in most patients (96.7 %). No significant differences were observed with regard to the severity and frequency of fibrosis of various degrees in the groups: mild, moderate, severe and full fibrosis was detected in 6.7 %, 20.0 %, 16.7 % and 56.6 %, respectively. The study of the localization of proapoptotic nucleases in the structures of the pancreas showed proapoptotic nucleases of DNA-ase I to be exclusively located in the cytoplasm of pancreatic acinar cells. At all stages of CP fibrosis, single acinar cells with translocation of the nuclease from the cytoplasm into the cell nucleus were found in the lobes of the pancreas. Endonuclease-G was found in large numbers in the cytoplasm of pancreatic islets, with it lower number being detected in the cytoplasm of the epithelial cells of the ducts. Conclusions. In CP, proapoptotic proteases of DNase I and endonuclease G are expressed in the cytoplasm of cells located in different pancreas zones. Thus, DNase I is expressed in the cytoplasm of acinar cells, while endonuclease G is most typical for insular cells and those in the epithelium of the ducts. This proves the existence of various apoptosis mechanisms in the exo- and endocrine portions of the pancreas.